2023
DOI: 10.3390/ijerph20043770
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Vinyasa Yoga Practice on the Well-Being of Breast-Cancer Patients during COVID-19 Pandemic

Abstract: Background: Vinyasa yoga practice improves body fitness and potentially positively affects practitioners’ well-being and health. Due to the diverse intensity of practice and positions customized to the practitioner’s needs, it can also support cancer patients. Undertaking physical activity that has a potentially positive effect on well-being and health was particularly important during the self-isolation that followed the COVID-19 pandemic. The purpose of this study was to evaluate the impact of three-month mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 100 publications
0
6
0
Order By: Relevance
“…Significantly few people indicated that spiritual motivation is the main reason for exercise ( Figure 4 ). Vinyasa yoga is a dynamic style characterized by the diversity that allows practitioners to choose the intensity of the practice according to their needs and abilities ( 37 , 73 , 74 ). The impact of vinyasa yoga practice on reducing stress and reducing problems with falling asleep has already been shown in a study on a group of oncologists who declared an improvement in well-being after 3 months of practice ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Significantly few people indicated that spiritual motivation is the main reason for exercise ( Figure 4 ). Vinyasa yoga is a dynamic style characterized by the diversity that allows practitioners to choose the intensity of the practice according to their needs and abilities ( 37 , 73 , 74 ). The impact of vinyasa yoga practice on reducing stress and reducing problems with falling asleep has already been shown in a study on a group of oncologists who declared an improvement in well-being after 3 months of practice ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Vinyasa yoga is a dynamic style characterized by the diversity that allows practitioners to choose the intensity of the practice according to their needs and abilities ( 37 , 73 , 74 ). The impact of vinyasa yoga practice on reducing stress and reducing problems with falling asleep has already been shown in a study on a group of oncologists who declared an improvement in well-being after 3 months of practice ( 37 ). Notably, in clusters 4 and 5 ( Figure 3 ), the respondents to whom the desire to reduce stress through yoga practice was assigned were predominantly those with a short history of the practice allowing us to assume, as confirmed by the results of other researchers, that yoga has a positive effect on stress management role ( 67 , 75 , 76 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has revealed high correlation between various measures of mindfulness and measures of subjective well-being [8]. Numerous researchers [9,10] have recognised that mindfulness-based techniques, such as yoga and meditation, lead to an increase in individuals' well-being. A few studies [11], conducted on a sample comprising college students, have reflected that mindfulness may influence subjective well-being via different mediating variables, namely self-esteem, core self-evaluation, optimism, and emotional intelligence.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, yoga training for people with PD includes Hatha yoga [ 14 ], Iyengar yoga [ 15 ], flow yoga [ 16 ], or Ashtanga yoga [ 17 ], of which Hatha yoga is the most widely used, followed by Iyengar yoga. Settings for yoga training include rehabilitation centers, yoga studios, home settings, and community service centers [ 18 ].…”
Section: Introductionmentioning
confidence: 99%